Develop a Pattern Algorithm to Construct Respiration Signal Using ECG Components - Sallo, Dilshad H. (Science Journal of University of Zakho, 2019)
The aim of this paper is designing an algorithm dubbed "pattern" to detect electrocardiogram (ECG) components accurately by searching exactly in the right places of peaks and getting exhaustive information related to the heart. Then, using the obtained results to propose a method for constructing respiration signal properly, by calculating the mean of R peaks to determine inspiration and expiration phases and calculating the amount of change for other peaks to be added during inspiration phase and subtracted during the expiration phase. The proposed method improves envelope method which only depends on the size of R to construct respiration signals. The results show that the pattern algorithm is guaranteed method and useful for detecting ECG components and exploiting them for constructing respiration signal work better than envelope method.